The Characterization of Disease Severity Associated IgG Subclasses Response in COVID-19 Patients - Luo, Huanle; Jia, Tingting; Chen, Jiamin; Zeng, Shike; Qiu, Zengzhao; Wu, Shu; Li, Xu; Lei, Yuxuan; Wang, Xin; Wu, Weihua; Zhang, Renli; Zou, Xuan; et al. (Frontiers in Immunology, 2021)
Increasing evidence suggests that dysregulated immune responses are associated with the clinical outcome of coronavirus disease 2019 (COVID-19). Nucleocapsid protein (NP)-, spike (S)-, receptor binding domain (RBD)- specific immunoglobulin (Ig) isotypes, IgG subclasses and neutralizing antibody (NAb) were analyzed in 123 serum from 63 hospitalized patients with severe, moderate, mild or asymptomatic COVID-19. Mild to modest correlations were found between disease severity and antigen specific IgG subclasses, of which IgG1 and IgG3 were negatively associated with viral load. Multiple cytokines were significantly related with antigen-specific Ig isotypes and IgG subclasses, and IL-1β was positively correlated with most antibodies. Furthermore, the old patients (≥ 60 years old) had higher levels of chemokines, increased NAb activities and SARS-CoV-2 specific IgG1, and IgG3 responses and compromised T cell responses compared to the young patients (≤ 18 years old), which are related with more severe cases. Higher IgG1 and IgG3 were found in COVID-19 patients with comorbidities while biological sex had no effect on IgG subclasses. Overall, we have identified diseases severity related higher antibodies which might not be caused by viral load, and cytokines were significantly associated with antibody response. Further, advancing age, comorbidities had obvious effect on IgG1 and IgG3.